ETHICAL DECISION-MAKING IN PROFESSIONAL CONSULTATIVE PRACTICE: A SCHOOL PSYCHOLOGY PERSPECTIVE - Hildebrand, Denise; Saklofske, Donald H.; von Baeyer, Carl L.; Yackulic, R.A. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1995)
ABSTRACT. The purpose of this study was to investigate the ethical understanding of school psychologists and, more particularly, their ability to identify ethical issues within their consultative practice. The researchers also sought to determine whether the differences between consultative orientations (e.g., psychometrician versus problem-solver) would influence the ability to identify ethical issues. The results of the study indicated that the ability to identify ethical issues varies between individuals and across situations and that the ethical dilemmas themselves appear to influence the identification of issues. Further, the researchers determined that there were no substantial differences between school psychologists’ consultative orientations in their ability to identify ethical issues. Based upon the results of the study, the term "ethical" was categorized according to three ethical decision-making orientations: value-oriented, rule-oriented, and intuitive. Finally, the implications regarding the measurement of ethical understanding and the development of guidelines for school psychological consultation are discussed in the paper. RÉSUMÉ. Cette étude visait à étudier la compréhension que les psychologues scolaires ont des questions d’éthique et, plus particulièrement, leur capacité à discerner les questions d’éthique qui surgissent dans leur pratique de consultation. Les chercheurs ont également tenté de détetminer si les différentes orientations des intervenants (p. ex., psychométrie par opposition à résolution de problèmes) ont un effet sur la capacité de discerner les questions d’éthique. Les résultats révèlent que la capacité à discerner les questions d’éthique varie selon les individus et les situations et que les delemmes éthiques eux-mêmes semblent affecter l’identification des questions. De plus, les chercheurs ont établi qu’il n’y a aucune différence importante entre les psychologues scolaires d’orientations diverses quant à leur capacité à identifier les questions d’éthique. En se fondant sur les résultats de l’étude, les auteurs ont catégorisé le tetme "éthique" en fonction de trois orientations régissant la prise de décision en ce domaine: orientation axée sur les valeurs, orientation axée sur les règles et orientation intuitive. Enfin, les auteurs traitent des répercussions de la mesure de la compréhension des questions d’éthique et de la formulation de lignes directrices à l’intention des psychologues scolaires.